Vinorelbine with trastuzumab in the treatment of metastatic breast cancer - Głogowska, Iwona; Dubiański, Roman; Sienkiewicz-Kozłowska, Renata; Murawska, Magdalena; Pieńkowski, Tadeusz (Contemporary Oncology/Współczesna Onkologia, 2009)
Aims: The purpose of this retrospective study was to evaluate the efficacy and safety of vinorelbine and trastuzumab combination chemotherapy in patients with HER2-overexpressing metastatic breast cancer. Material and methods: From January 2003 to December 2007, 175 patients with locally advanced or metastatic breast cancer started receiving combination therapy with vinorelbine plus trastuzumab. Overexpression of HER2 receptor was confirmed in all patients. Vinorelbine was administered weekly in a dose of 25 mg/m 2 (n = 137) or 30 mg/m 2 (n = 24), and trastuzumab in a loading dose 4 mg/kg, and then 2 mg/kg weekly. After combined treat-ment with vinorelbine trastuzumab was given in monotherapy to disease prog-ression or unacceptable toxicity. Results: The overall response rate (ORR) was 59% (n = 106) and 78% (n = 137) of patients obtaining clinical benefit. Median overall survival (mOS) was 95 weeks. Progression of the disease was observed in 158 cases and me- dian time to progression (mTTP) was 27 weeks. There was a statistically significant correlation between mTTP and number of metastases, number of previous lines of palliative treatment and number of previous combinations of trastuzumab with cytostatic agents. Conclusions: Trastuzumab in com-bination with vinorelbine is an effective and generally well-tolerated regimen in the treatment of metastatic breast cancer with overexpression of HER2 receptor (ORR 59%, CB 78%, mTTP 27 weeks), especially in the first line treatment of less advanced cancer.